2013
DOI: 10.1007/s10577-013-9342-3
|View full text |Cite
|
Sign up to set email alerts
|

High chromosome variability and the presence of multivalent associations in buthid scorpions

Abstract: In this study, we investigated the mitotic and meiotic chromosomes of 11 Buthidae scorpion species, belonging to three genera (Ananteris, Rhopalurus and Tityus), to obtain detailed knowledge regarding the mechanisms underlying the intraspecific and/or interspecific diversity of chromosome number and the origin of the complex chromosome associations observed during meiosis. The chromosomes of all species did not exhibit a localised centromere region and presented synaptic and achiasmatic behaviour during meiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 37 publications
11
70
1
Order By: Relevance
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique.…”
Section: Discussionmentioning
confidence: 99%
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were dissected in saline solution (128.3 m M NaCl, 16.7 m M Na 2 HPO 4 , 19.9 m M KH 2 PO 4 ), and the testes were removed and divided into 2 parts. One part of each testis was used for light microscopy analyses [Mattos et al, 2013] and the other part was subjected to cellular microspreading to visualize the SCs and associated structures under transmission electron microscopy (TEM), according to Loidl and Jones [1986]. The microspread cells were silver-impregnated following Kodama et al [1980].…”
Section: Methodsmentioning
confidence: 99%
“…These rearrangements, when present in a heterozygous condition, result in multiple chromosomal associations during meiosis I, which can even involve all the chromosomes of the diploid set. As an additional peculiarity, all species of the family Buthidae have holocentric chromosomes [Shanahan, 1989a, b;Mattos et al, 2013;Schneider et al, 2014].…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
See 1 more Smart Citation
“…Both characters are typical for the scorpions from the family Buthidae (e.g. Mattos et al, 2013). The chromosomes of the first pair are significantly longer (13.41 % of the diploid (50), and movable finger dentition (51).…”
Section: Dimensions (Mm)mentioning
confidence: 99%